A Review of the Literature on the Global Epidemiology of Corneal Blindness. Issue 12 (December 2019) - Porth, Julia M.; Deiotte, Erin; Dunn, Matthew; Bashshur, Ramona
Abstract : Purpose: This study seeks to review published research on the global epidemiology of corneal blindness, with a specific focus on the available published estimates of incidence, prevalence, and trends in incidence or prevalence, as well as the contribution of corneal causes to overall burden of blindness. Methods: A scoping review was conducted of the published literature on the global epidemiology of corneal blindness, with emphasis on prevalence and incidence studies. Four databases were searched using both epidemiological and corneal blindness keywords. This review was limited to studies with a primary aim of determining the incidence, prevalence, or trends in corneal blindness or the percentage of blindness due to corneal causes. Only conditions considered to signify current blindness were included, not diseases that eventually could lead to blindness if left untreated. Results: A total of 185 articles met the selection criteria. Of these, 145 articles investigated all-cause blindness prevalence. Only 10 articles specifically aimed to determine estimates of corneal blindness prevalence, 7 articles provided results for all-cause blindness incidence, and no studies focused on obtaining corneal blindness incidence. Data on corneal blindness were most often present in studies investigating all-cause blindness and in trachoma studies. Conclusions: The results demonstrate the somewhat inconsistent and fragmented information regarding corneal causes of vision loss. A significant outcome of this research is the demonstration of a need for further research into global corneal blindness and the necessary steps to address the problem. Abstract : Supplemental Digital Content is Available in the Text.